2019
DOI: 10.9734/jamb/2019/45762
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Vaginal Candidiasis in Pregnant and Non-Pregnant Women Attending Ibrahim Badamasi Babangida Specialist Hospital and General Hospital, Minna Niger State, Nigeria

Abstract: This work was carried out in collaboration between the authors. Author KTM carried out the sample collection, designed the study template, managed the literature searches and prepared the manuscripts for publication. Author MEA carried out the biochemical analysis, statistical analysis, and discussion of results. The authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…While our results were lower than (55.4%) those obtained in Cameroon ( 16) and even very much lower than (92%) in a report from Libya (17). Feyi (18) in Tanzania and Menza et al (19) in Kenya reported prevalence rates in agreement with our result; they reported that, prevalence of vaginal candidiasis among pregnant women were 42.9% , 42.7% respectively.…”
Section: Discussionsupporting
confidence: 92%
“…While our results were lower than (55.4%) those obtained in Cameroon ( 16) and even very much lower than (92%) in a report from Libya (17). Feyi (18) in Tanzania and Menza et al (19) in Kenya reported prevalence rates in agreement with our result; they reported that, prevalence of vaginal candidiasis among pregnant women were 42.9% , 42.7% respectively.…”
Section: Discussionsupporting
confidence: 92%
“…We can also observe the formation of pseudohyphae in some of the isolates. This is a basic identification test for fungi (39).…”
Section: Resultsmentioning
confidence: 99%
“…We can also observe the formation of pseudohyphae in some of the isolates. This is a basic identification test for fungi [ 59 ].…”
Section: Resultsmentioning
confidence: 99%